Community, economic creativity, and organization - Amin, Ash.; Roberts, Joanne (Oxford : Oxford University Press, 2008)
'Communities of practice', like 'social capital' and 'networks' is an idea that has been widely adopted in the social sciences particularly in discussion of innovation and creativity. This text evaluates the concept and its uses, and will be an essential guide for students and researchers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Communities of practice; Organizational learning